Implementation of point-of-care ultrasound in the medical intensive care unit: A retrospective analysis of physician practices and patient outcomes - Sam Tierney; Stephen Germana; Frank Papik; Werda Alam; Abigail Chua; Sunil Chulani; Karin Hasegawa; Xiaoyue Zhang; Sahar Ahmad (PLoS ONE, 2025)
Background Point of care ultrasound (POCUS) use has become ubiquitous in the ICU setting. Despite this, there remains a paucity of data regarding how its use impacts patient outcomes. We sought to determine if physician attitudes toward and use of POCUS impact patient outcomes. Objectives To evaluate the impact of physician use of POCUS in the medical intensive care unit (MICU) on patient care outcomes. Methods A longitudinal, single-center retrospective study of adult patients in a tertiary care center MICU was conducted between 2016 and 2017. A total of 512 patient encounters were analyzed for: number of ventilator days, number of vasopressor days, and MICU length of stay. The outcomes were then compared between attending physicians who showed high, medium, and low self-reported POCUS implementation and confidence scores by questionnaire. Results Patients of physicians in the low POCUS confidence group had a statistically significant increase in MICU length of stay (IRR = 1.19, 95% CI: 1.06–1.32, p = 0.0022) and ventilator days (IRR = 1.18, 95% CI: 1.03–1.36, p = 0.0197) compared to the medium confidence group. Conclusions Our investigation found a statistically significant relationship between self-reported confidence in POCUS by MICU physicians and MICU length of stay as well as total days spent on mechanical ventilation. Increased self-reported use of POCUS by physicians did not impact patient outcomes in this population. There was similarly no evidence of increased harm or adverse outcomes in high-POCUS implementation groups.